Proceedings of the 2018 International Conference on Network, Communication, Computer Engineering (NCCE 2018) 2018
DOI: 10.2991/ncce-18.2018.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Lane Width to Speed for Urban Expressway: A Case Study in Shanghai

Abstract: Abstract. In order to mitigate traffic congestions caused by the rapidly increased private car ownership in Shanghai, the transportation agencies implemented several strategies, such as narrowed the lane width to create additional lanes. To investigate the relationship of the lane width to speed, two month of traffic data are collected from 36 sites in the management system of Shanghai expressways. The ANOVA analysis and regression analysis are used to evaluate the effect of average lane width on speed at diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
0
1
Order By: Relevance
“…Also, on the extra-urban tangents, it was shown that the pavement width proportionally affects the operating speed. Contrary to research [75][76][77], Fitzpatrick et al (2005) [34] did not find a statistically significant relationship between operating speed and road lane width. Maji et al ( 2020) [46] conducted research at 251 locations in Oklahoma and created three operating speed prediction models for roads with a higher speed limit (80-105 km/h), for roads with a lower speed limit (56-72 km/h) and for roads with various speed limits, the last of which proved to be the most accurate.…”
Section: Tangent Length (M) V 85t (Km/h)contrasting
confidence: 97%
“…Also, on the extra-urban tangents, it was shown that the pavement width proportionally affects the operating speed. Contrary to research [75][76][77], Fitzpatrick et al (2005) [34] did not find a statistically significant relationship between operating speed and road lane width. Maji et al ( 2020) [46] conducted research at 251 locations in Oklahoma and created three operating speed prediction models for roads with a higher speed limit (80-105 km/h), for roads with a lower speed limit (56-72 km/h) and for roads with various speed limits, the last of which proved to be the most accurate.…”
Section: Tangent Length (M) V 85t (Km/h)contrasting
confidence: 97%